2005
DOI: 10.1152/japplphysiol.00870.2004
|View full text |Cite
|
Sign up to set email alerts
|

Aging does not alter the mechanosensitivity of the p38, p70S6k, and JNK2 signaling pathways in skeletal muscle

Abstract: The capacity for skeletal muscle to recover its mass following periods of unloading (regrowth) has been reported to decline with age. Although the mechanisms responsible for the impaired regrowth are not known, it has been suggested that aged muscles have a diminished capacity to sense and subsequently respond to a given amount of mechanical stimuli (mechanosensitivity). To test this hypothesis, extensor digitorum longus muscles from young (2-3 mo) and old (26-27 mo) mice were subjected to intermittent 15% pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 20 publications
2
35
2
Order By: Relevance
“…Maximum isometric tetanic force was determined in EDL muscles from mice [wild type (n = 4), Clock Δ19 (n = 7), Bmal1 −/− (n = 3), and MyoD −/− (n = 4)] following procedures described previously (43).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximum isometric tetanic force was determined in EDL muscles from mice [wild type (n = 4), Clock Δ19 (n = 7), Bmal1 −/− (n = 3), and MyoD −/− (n = 4)] following procedures described previously (43).…”
Section: Methodsmentioning
confidence: 99%
“…Skeletal muscle was homogenized in lysis buffer, and samples were electrophoresed on 10% SDS/PAGE and transferred to PVDF membrane (Millipore) as described previously (43). Membranes were incubated with a polyclonal antibody against MyoD (Santa Cruz Biotechnology) or γ-tubulin (Sigma-Aldrich) followed by incubation with alkaline phosphatase-linked anti-rabbit antibody or anti-mouse antibody (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, recent work showing increased p70 S6K phosphorylation with stretch activated mechanotransduction in skeletal muscle suggests that eccentric loading may be critical for S6K1 activation and therefore hypertrophy (Hornberger et al 2005a;Hornberger et al 2005b;Spangenburg and McBride 2006).…”
Section: A; Ruvinsky and Meyuhas 2006) Mammalian Cells Express Tmentioning
confidence: 99%
“…It has been shown that mechanical stimulation activates p38 in muscle (Boppart et al, 2001;Hornberger et al, 2005) and in myoblasts that have undergone 2 days of differentiation (Rauch and Loughna, 2005). However, the mechanism whereby mechanical stimulation activates p38 in muscle cells Skeletal muscle responds to mechanical stimulation by activating p38 MAPK, a key signal for myogenesis.…”
Section: Introductionmentioning
confidence: 99%